Kuchman I. M. Linguistic and lingual status of category of causativity - Kuchman I. M. (Philological Treatises, 2020)
The article gives an outline of history of studies of causativity category in domestic and foreign linguistics, highlights the variety of ways and approaches to analysis of the problem of causative relations, defines the register and status of multilevel units of expressing category of causativity in modern Ukrainian language